2021
DOI: 10.1016/j.clnesp.2021.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of adipose tissues by Dual-Energy X-Ray Absorptiometry and Computed Tomography in colorectal cancer patients

Abstract: Background & aims: Excess adipose tissue may affect colorectal cancer (CRC) patients' disease progression and treatment. In contrast to the commonly used anthropometric measurements, Dual-Energy X-Ray Absorptiometry (DXA) and Computed Tomography (CT) can differentiate adipose tissues. However, these modalities are rarely used in the clinic despite providing high-quality estimates. This study aimed to compare DXA's measurement of abdominal visceral adipose tissue (VAT) and fat mass (FM) against a corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…A single slice at L3 is frequently used in research settings because of its high association with whole‐body measurements 36,37 and abdominal volume 38 . We have previously shown that although a single slice at L3 is highly associated with abdominal VAT volume, the use of multiple slices (L2, L3, and L4) increased the explained variance against VAT volume 38 . However, BodySegAI was trained and tested on multiple slices at different anatomical levels (L2 to S1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A single slice at L3 is frequently used in research settings because of its high association with whole‐body measurements 36,37 and abdominal volume 38 . We have previously shown that although a single slice at L3 is highly associated with abdominal VAT volume, the use of multiple slices (L2, L3, and L4) increased the explained variance against VAT volume 38 . However, BodySegAI was trained and tested on multiple slices at different anatomical levels (L2 to S1).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the comprehensive task of semi‐manual segmentation for establishing the human ground truth and lack of standardized regions of interest, BodySegAI was only tested on single CT slices from predefined anatomical regions (L2 to S1), not entire abdominal volumes. However, the model can readily be used for volumetric data, which is proposed to further increase the accuracy compared with the usage of single slices only 38 . Although we consider BodySegAI as an automatic software, the axial CT slices still have to be manually extracted from the CT examination and uploaded into BodySegAI in order for the body composition analysis to be conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Beginning around 2020, numerous studies have leveraged deep learning to perform automatic fat quantification. [10][11][12][13][14][15][16][17][18][19][20] Regarding the second limitation, patient radiation exposure, the guiding principle of medical imaging has been "as low as reasonably achievable" (ALARA). Yamada et al reported the lower limit of radiation dose of CT images for manual fat quantification.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the reports on automated fat quantification methods provide insufficient information on radiation dose or use doses used for routine abdominal scans. [11][12][13][14][16][17][18][19][20] Since the early 2010′s, Pickhardt et al have published a series of reports on the application of fat quantification to abdominal CT for the purpose of colorectal cancer prevention and screening, using the CT colonoscopy (CTC) technique. 10,12,22,23 Performing opportunistic fat quantification screening on CTC images is one method of obtaining fat quantification information without additional radiation exposure.…”
Section: Introductionmentioning
confidence: 99%